#### Answer

a. $48x^{2a}$
b. $y^{10b+3}$

#### Work Step by Step

a.
$3x^{4a}(4x^{-a})^2$
$=3x^{4a}(4^2x^{-2a})$
$=(3)(4^2)(x^{4a-2a})$
$=(48)(x^{2a})$
$=48x^{2a}$
b.
$\frac{(y^{4b})^3}{y^{2b-3}}$
$=\frac{y^{12b}}{y^{2b-3}}$
$=y^{12b-(2b-3)}$
$=y^{10b+3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

a. $48x^{2a}$
b. $y^{10b+3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.